PENERAPAN HIGH ORDER THINKING SKILL DALAM MODEL PEMBELAJARANSMALL GROUP DISCUSSION UNTUK MENINGKATKAN HASIL BELAJARPPKN KELAS 5 SEKOLAH DASAR - Bernandito Prihanda Ngongo (Journal for Lesson and Learning Studies, 2018)
Abstrak            Penelitian ini bertujuan untuk meningkatkan hasil belajar PPKn kelas 5 SD melalui penerapan HOTS dalam model pembelajaran Small Group Discussion. Metode penelitian yang digunakan adalah PTK (Penelitian Tindakan Kelas).Teknik pengumpulan data menggunakan tes, observasi, dan  studidokumen. Instrumen yang digunakan adalah lembar observasi aktivitas guru, lembar observasi aktivitas siswa, dan tes hasil belajar.Teknik analisis data yang digunakan yaitu deskriptif kualitatif dan kuantitatif.Subjek penelitian adalah kelas V SDN Sumogawe 03 Kabupaten Semarang Tahun Ajaran 2017/2018.Hasil penelitian menunjukkan bahwa dengan penerapan High Order Thinking Skill dalam model pembelajaran Small Group Discussion dapat meningkatkan hasil belajar PPKn siswa.Secara klasikal hasil belajar PPKn siswa mengalami peningkatan dengan persentase nilai yang diperoleh pada siklus I persentase yang diperoleh sebesar 50% dan siklus II sebesar 70%. Sehingga, dapat disimpulkan bahwa penerapan High Order Thinking Skill dalam model pembelajaran Small Group Discussiondapat meningkatkan hasil belajar PPKnkelas 5 Sekolah Dasar. Kata Kunci: High Order Thinking Skill,Small Group Discussion, Hasil Belajar, dan PPKn. ABSTRACTThis research aims to improve the results of studying Pancasila and Citizenship Education of the fifth grade of primary school through the HOTS application within a learning model of Small Group Discussion. The research method used is CAR (Class Action Research). The collection of data technique uses test, observation, and documents’ study. The instruments used are observation sheets, teacher activity,  observation sheets  of student activity, and the test of studying results. The analysis of data technique used i.e. qualitative descriptive and quantitative. The subject of research is the fifth grade students of National Elementary Schools of Sumogawe 03 Semarang Regency, school year 2017/2018. The results of research shows that with the application of High-Order Thinking Skills within the learning model of Small Group Discussion is able to improve the results of studying Pancasila and Citizenship Education of the student. Classically, the result of studying Pancasila and Citizenship Education of the student getting an improvement with a values’ percentage  obtained on the first cycle at 50%  and on the second cycle  at 70%. So that, it is inferential that the application of High-Order Thinking Skills within the learning model of  Small Group Discussion is able to improve the results of studying Pancasila and  Citizenship Education of the fifth grade student of the elementary school. Key Words:High-Order Thinking Skills,Small Group Discussion, the results of the study, andPancasila and Citizenship Education.